2015
DOI: 10.1007/s12012-015-9329-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Associated with Ischemic Stroke in Diabetes Mellitus Patients

Abstract: Diabetes is an established risk factor for ischemic stroke, but the associated molecular mechanisms remain to be fully elucidated. This study investigated the role of plasma and platelet microRNAs and their targeting proteins in the activation of platelets and their association with the occurrence of ischemic stroke in patients with type 2 diabetes mellitus (T2DM). Results showed that the expressions of platelet and plasma miR-144 and miR-223 were significantly altered in T2DM patients with or without ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…Karolina et al (8) experimentally demonstrated that IRS1 is the target of miR-144, and that increased circulating levels of miR-144 are correlated with downregulation of its predicted target, IRS1, at the mRNA and protein levels. Similar results were reported by Yang et al (33). Furthermore, Jeong et al (36) and Wang et al (37) revealed that IRS1 is also the target of miR-96.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Karolina et al (8) experimentally demonstrated that IRS1 is the target of miR-144, and that increased circulating levels of miR-144 are correlated with downregulation of its predicted target, IRS1, at the mRNA and protein levels. Similar results were reported by Yang et al (33). Furthermore, Jeong et al (36) and Wang et al (37) revealed that IRS1 is also the target of miR-96.…”
Section: Discussionsupporting
confidence: 92%
“…Wang et al (23) found that a higher expression of miR-144 in plasma was significantly associated with T2DM in Sweden. Similar results were reported by Yang et al (33), and Zhu and Leung (34) showed that the upregulation of circulating miR-144 may be a potential biomarker for T2DM in a meta-analysis of controlled profiling studies. Karolina et al (8) found that miR-144 was significantly increased in blood samples from a T2DM rat model.…”
Section: Discussionsupporting
confidence: 88%
“…Circulating miRNAs have also been studied as diagnostic biomarkers for diabetes-related stroke (Yang et al, 2016a; Duan et al, 2014). Decreased expression of miR-223 and miR-146a was observed in both the plasma and platelets in diabetic stroke patients compared to non-diabetic stroke patients and was correlated with higher blood glucose concentration and platelet activation rates (Duan et al, 2014).…”
Section: Micrornas As Stroke Biomarkersmentioning
confidence: 99%
“…Decreased expression of miR-223 and miR-146a was observed in both the plasma and platelets in diabetic stroke patients compared to non-diabetic stroke patients and was correlated with higher blood glucose concentration and platelet activation rates (Duan et al, 2014). Increased miR-223 and decreased levels of miR-144 in platelets and plasma was thought to indicate a risk for ischemic stroke in type-2 diabetics (Yang et al, 2016a). Post-stroke depression is a common complication that is associated with increased morbidity and mortality (Whyte and Mulsant, 2002).…”
Section: Micrornas As Stroke Biomarkersmentioning
confidence: 99%
“…The miR-144 level in platelets is higher in diabetes mellitus type 2 (T2DM) patients with ischemic stroke. The platelet miR-223 expression decreases in this group in comparison to T2DM patients without thromboembolic complications [52]. In other study performed by Duan et al [53] the expressions of platelet miR-223 and miR-146a in patients with diabetes mellitus and ischemic stroke were significantly lower than in healthy donors.…”
Section: Platelets Mirna and Thrombotic Complicationsmentioning
confidence: 70%